Answer:
x = -62.5
Step-by-step explanation:
y = kx
-4 = k(25)
k = -4/25
y = (-4/25)x
10 = (-4/25)x
x = 10 × 25/-4
x = -62.5
Answer:
(2x + 3)(x - 2)
Step-by-step explanation:
use FOIL
First, Outside, Inside, Last
2x x x = 2x²
2x x -2 = -4x
3 x x = 3x
3 x -2 = -6
2x² - 4x + 3x - 6
And what else is in the problem I do not get what the problem is
Answer:
C.
Step-by-step explanation:
-a + b = -2
b = a + 3
-a + a + 3 = -2
3 = -2 (incorrect).....no solutions.....because these lines are parallel
Answer:
6(3x + 1/2)
9(2x + 1/3)
2(9x + 5) - 7
Step-by-step explanation:
6(3x + 1/2)= 18x + 3 ✅
9(2x + 1/3)= 18x + 3 ✅
4(4x + 1) -1= 16x + 3
2(9x + 5) - 7= 18x + 3 ✅
3(6x + 2) + 3= 18x + 9